A NEW NATURAL HYBRID OF NEPENTHES FROM MT. KINABALU ( SABAH ) - Jummat H. Adam; C.C Wilcock (Research Center for Biology, 1992)
A new natural hybrid of Nepenthes, N. x alisaputraiana, from Mt. Kina-balu Sabah is described.